CircHTT(2,3,4,5,6) - co-evolving with the HTT CAG-repeat tract: modulates Huntington's disease phenotypes - Morandell, Jasmin; Monziani, Alan; Lazioli, Martina; Donzel, Deborah; Döring, Jessica; Oss Pegorar, Claudio; D’Anzi, Angela; Pellegrini, Miguel; Mattiello, Andrea; Bortolotti, Dalia; Bergonzoni, Guendalina; Tripathi, Takshashila; et al. (Molecular therapy. Nucleic Acids, 2024)
Circular RNA (circRNA) molecules have critical functions during brain development and in brain-related disorders. Here, we identified and validated a circRNA, circHTT(2,3,4,5,6), stemming from the Huntington’s disease (HD) gene locus that is most abundant in the central nervous system (CNS). We uncovered its evolutionary conservation in diverse mammalian species, and a correlation between circHTT(2,3,4,5,6) levels and the length of the CAG-repeat tract in exon-1 of HTT in human and mouse HD model systems. The mouse orthologue, circHtt(2,3,4,5,6), is expressed during embryogenesis, increases during nervous system development, and is aberrantly upregulated in the presence of the expanded CAG tract. While an IRES-like motif was predicted in circHTT(2,3,4,5,6), the circRNA does not appear to be translated in adult mouse brain tissue. Nonetheless, a modest, but consistent fraction of circHtt(2,3,4,5,6) associates with the 40S ribosomal subunit, suggesting a possible role in the regulation of protein translation. Finally, circHtt(2,3,4,5,6) overexpression experiments in HD-relevant STHdh striatal cells revealed its ability to modulate CAG expansion-driven cellular defects in cell-to-substrate adhesion, thus uncovering an unconventional modifier of HD pathology.